POTENCIAIS FOTOPROTETOR E ANTIOXIDANTE DE BLENDS DE CHÁS - DA ROSA, Juliano Santos; DE CASTRO, Thiago Luis Aguayo; MASCARENHAS, Maria do Socorro; CARDOSO, Claudia Andrea Lima Cardoso (ANAIS DO ENIC, 2024)
-